1992
DOI: 10.1161/01.hyp.19.2_suppl.ii10
|View full text |Cite
|
Sign up to set email alerts
|

Localization of components of the kallikrein-kinin system in the kidney: relation to renal function. State of the art lecture.

Abstract: T he renal kallikrein-kinin system (KKS) is a complex multienzymatic system, the main components of which are the enzyme kallikrein, the substrate kininogen, effector hormones or kinins (lysyl-bradykinin, bradykinin), metabolizing enzymes (several kininases, the most relevant being kininases I and II [ACE] and neutral endopeptidase 24.11 [NEP]), and an as-yet unknown number of activators and inhibitors of kallikrein and kininases.The renal KKS seems to participate in both intrarenal and extrarenal complex eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…Bradykinin has been shown to be present in interstitial fluid from the cortex and medulla (35,36) and is excreted in urine (2), indicating that it is formed locally in the interstitium and/or in the tubular lumen of the collecting ducts. Kinin binding sites have been localized on renal tubular cells, most notably collecting tubules (21,37,42,43) and interstitial cells (14,46). Furthermore, the BKB 2 receptors have been localized to both the luminal and basolateral membranes of proximal and distal straight tubules, cortical connecting tubules, and cortical and medullary collecting ducts (11,43).…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin has been shown to be present in interstitial fluid from the cortex and medulla (35,36) and is excreted in urine (2), indicating that it is formed locally in the interstitium and/or in the tubular lumen of the collecting ducts. Kinin binding sites have been localized on renal tubular cells, most notably collecting tubules (21,37,42,43) and interstitial cells (14,46). Furthermore, the BKB 2 receptors have been localized to both the luminal and basolateral membranes of proximal and distal straight tubules, cortical connecting tubules, and cortical and medullary collecting ducts (11,43).…”
Section: Discussionmentioning
confidence: 99%
“…The kallikrein-kinin system is a vasoactive system that seems to participate in complex events such as regulation of blood pressure, control of the extracellular volume, sodium and water excretion, renal vascular resistance, and renin release. 16,17 We have previously demonstrated that urinary kallikrein is increased in normal rat pregnancy. 9,11 In the rat, the highest kallikrein levels are observed at midpregnancy, attaining prepregnancy values toward term.…”
Section: Salas Et Al Water Deprivation In Pregnant Rats 337mentioning
confidence: 97%
“…1 " 3 Intravenous administration of an inhibitor of neutral endopeptidase, the major kininase in the rat kidney, 4 selectively increased renal inner medullary (papillary) blood flow in anesthetized rats. 3 This effect was blocked by a kinin receptor antagonist, indicating that an elevation of endogenous kinins can alter medullary blood flow. Similar results have been demonstrated during angiotensin converting enzyme inhibition.…”
Section: Orphological and Functional Data Indicate Thatmentioning
confidence: 99%